2020
DOI: 10.1002/mco2.26
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus in human diseases: Mechanisms and advances in clinical treatment

Abstract: Coronaviruses (CoVs), a subfamily of coronavirinae, are a panel of single‐stranded RNA virus. Human coronavirus (HCoV) strains (HCoV‐229E, HCoV‐OC43, HCoV‐HKU1, HCoV‐NL63) usually cause mild upper respiratory diseases and are believed to be harmless. However, other HCoVs, associated with severe acute respiratory syndrome, Middle East respiratory syndrome, and COVID‐19, have been identified as important pathogens due to their potent infectivity and lethality worldwide. Moreover, currently, no effective antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 381 publications
(460 reference statements)
0
19
0
Order By: Relevance
“…The CoVs particles majorly consist of four different structural proteins, i.e., surface glycoprotein (S), membrane glycoprotein (M), envelope (E), and nucleocapsid (N) [7] , [8] while, some CoVs also encode auxiliary proteins which play remunerate functions. The homotrimeric class I fusion protein, namely S protein, allows the viral membrane to fuse with the host cell surface receptors angiotensin-converting enzyme 2 (ACE2), leading to fusion and viral entry [9] , [10] leading to SARS [11] . Additionally, SARS-CoV-2 has been reported to cause systemic infections in the digestive, circulatory, urogenital, and nervous system [12] .…”
Section: Introductionmentioning
confidence: 99%
“…The CoVs particles majorly consist of four different structural proteins, i.e., surface glycoprotein (S), membrane glycoprotein (M), envelope (E), and nucleocapsid (N) [7] , [8] while, some CoVs also encode auxiliary proteins which play remunerate functions. The homotrimeric class I fusion protein, namely S protein, allows the viral membrane to fuse with the host cell surface receptors angiotensin-converting enzyme 2 (ACE2), leading to fusion and viral entry [9] , [10] leading to SARS [11] . Additionally, SARS-CoV-2 has been reported to cause systemic infections in the digestive, circulatory, urogenital, and nervous system [12] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate and scale in which COVID-19 is spreading global far surpasses those of SARS or MERS. The absence of specific antiviral drugs or therapies against human coronaviruses stresses the importance of preventative measures in managing the spread of the virus [ 5 ]. Despite various countermeasures in place to curb the spread of the disease in many countries, including social distancing and mandatory face masks, the number of positive cases are still on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that corticosteroid was used to treat coronavirus diseases, including Middle East respiratory syndrome (MERS) and severe acute respiratory syndrome (SARS) [17]. Studies have demonstrated that cytokine reactions caused by the enormous release of cytokines were major cause of death in a number of cases of SARS and MER [18,19] and corticosteroids could have a positive antagonistic effect on the cytokine storm [20]. Azithromycin has immunomodulatory and antiviral properties that might be of attention in the treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%